2013
DOI: 10.1371/journal.pone.0081745
|View full text |Cite|
|
Sign up to set email alerts
|

Benign and Malignant Renal Cells Are Differentially Inhibited during Prolonged Organ Preservation

Abstract: The worry of potential residual renal cancer cells in donor kidney after resection of small renal cancer impedes the extensive use of such controversial donor source. To explore the impacts of organ preservation process on the survival of renal cancer cells, we detected cell proliferation and viability of benign and malignant renal cell lines and clinical renal samples after treated with simulated organ preservation process. It was found that the viability and proliferation of malignant renal cells are inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…However, this novel source remains arguable as the fear of tumour recurrence. Many pioneers have advocated the implementation of this novel source for kidney transplantation [19–22,25,41–44]. Cohn et al have campaigned a decade ago: ‘We encourage urologic oncologists to open discussions with transplant surgeons about considering transplantation of kidneys after ex vivo excision of small renal masses, from very selected donors (who prefer radical to partial nephrectomy) and into very selected (high‐risk) recipients’ [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this novel source remains arguable as the fear of tumour recurrence. Many pioneers have advocated the implementation of this novel source for kidney transplantation [19–22,25,41–44]. Cohn et al have campaigned a decade ago: ‘We encourage urologic oncologists to open discussions with transplant surgeons about considering transplantation of kidneys after ex vivo excision of small renal masses, from very selected donors (who prefer radical to partial nephrectomy) and into very selected (high‐risk) recipients’ [42].…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, Yu et al have conducted a study aiming to test the viability of tumour cell after cold perfusion and preservation. It was found that the viability of tumour cell is much lower than normal renal tubular cell after cold perfusion and preservation [41]. Nevertheless, the tumour recurrence is always a risk after tumour excision and a strict protocol is mandatory for surveillance.…”
Section: Discussionmentioning
confidence: 99%